Building a Trauma-Informed Workforce Capacity and Legacy. Issue 1 (1st January 2017) - Popescu, Marciana; Strand, Virginia; Way, Ineke; Williams-Hecksel, Cheryl; Abramovitz, Robert
ABSTRACT: Social workers encounter trauma in a majority of the populations they serve. It is therefore essential to train social work students to understand the impact of trauma, to assess trauma history and symptoms, and to effectively intervene with children and families. This article presents 3 qualitative research narratives that provide an in-depth analysis of factors contributing to successful implementation of an innovative trauma-informed educational model. The narratives identify common themes related to student knowledge and field readiness; personal and system context; organizational leadership; and vision, training, and partnerships/collaborations.